Development of Zinc/MCM-41/air microbattery and investigation of its humidity sensing characteristic - Saputra, Hens (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
MCM-41 inorganic membrane is introduced as a new separator material for electrochemical cells. MCM-41 material which consists of arrays of hexagonal nanochannels is expected to substitute the customary polymeric membrane as the electrochemical cell separator. Its regular arrays of nano-channels could provide the ion exchange pathways. Furthermore, it also acts as the electrolyte vehicle due to the hydrophilic and along with the high surface area and pore volume density characteristics. The MCM-41 membrane is synthesized onto zinc substrate by dipcoating method from a parent solution consisted of quarternary ammonium surfactant, cethyltrimethylammonium bromide C16H33(CH3)3NBr (CTAB), hydrochloric acid (HCl), deionized water (H2O), ethanol (C2H5OH), and tetraethylortosilicate (TEOS) with molar ratio formulation of 0.05 CTAB, 1.0 TEOS, 0.5 HCl, 25 C2H5OH and 75 H2O. The structural formation of MCM-41 material is verified by the X-ray diffraction measurement. The Brunauer-Emmett-Teller (BET) surface area of assynthesized MCM-41 is found to be 1200 m2 g-1 and the pore volume is 1.08 cm3 g-1. The BJH pore size distribution indicates a sharp curve centred around 2 nm, which is supported by permporometry analysis and Transmission Electron Microscopy (TEM) observations. A feasible, thin, compact Zn/MCM-41/air cell design with high discharge capability is demonstrated. The performance characteristics of the cell are comparable to the published product datasheet of commercial zinc-air button cells of equivalent size. Zn/MCM-41/air cell of monopolar design, measured 1 cm2 area, ca. 300 μm thick and weighed 50 mg, possesses the following properties: open circuit voltage (OCV) of 1.5 V, limiting current density of 42 mA cm-2, optimum power density of 40 mW cm-2, and volumetric energy density of 840 Wh l-1 rated at 20 mA. Moreover, utilizing a bipolar design, a high discharge rate Zn/MCM-41/air cell is produced. The cell is capable to deliver a maximum current density of 100 mA cm-2 and an optimum power of 110 mW cm-2. In order to employ MCM-41 membrane separator in alkaline electrochemical cells, the quantity of potassium hydroxide (KOH) electrolyte has to be limited to at most 70 wt. % KOH. It is noticed that for within 30 wt. % of KOH, the hexagonally ordered nanostructure of MCM-41 still exists though evidence of caustic alkali attack was observed. Interestingly, with increasing KOH content MCM-41 ordered network do not immediately collapse but transformed gradually into MCM-50 lamellar gel structure. This phenomenon has never been reported elsewhere. Beyond 70 wt. % of KOH, the ordered network totally diminishes. A novel application for Zn/MCM-41/air cell is discovered. The cell, in its dry form without the inclusion of KOH electrolyte, generates OCV value once exposed to ambient air moisture. The OCV of the cell shows a linear dependence on relative humidity content above 60 % and most likely for humidity content below 45 %. This is due to the water adsorption-desorption characteristics of mesoporous MCM-41 material. Comparison between relative humidity data obtained from commercial digital humidity sensor with data deduced from OCV readings of the Zn/MCM-41/air cell shows good sensitivity and high reliability.